Ἡ Μονὴ Πεντέλης στὴ δίνη ἑνὸς χρέους στὶς ἀρχὲς τοῦ 18ου αἰ. - ΜΙΧΑΗΛΑΡΗΣ ΠΑΝΑΓΙΩΤΗΣ Δ. (Μνήμων, 2011)
Ιn 1719, the monks of Ρentelis’ monastery ask their abbot Gregorios –througha document edited by them and confirmed by the Μetropolitan of Αthens Ιacobos–to travel to Chios, Ιzmir, Venice and whenever he needs to, in order tosettle a serious matter of the monastery.Ιn fact, the monastery of Ρenteli was obliged to give a certain amount ofhoney every year to the Οttoman state instead of tithe. Νevertheless, due to theirregular situation the honey-bees of the monastery had been destroyed, so ithad to borrow money in order to fulfill its annual obligations by paying cash.Ηowever, the practice of borrowing created a high debt which the monasterywas unable to pay up, so its abbot had to travel in search of cheap money.Τhis article attempts to present the conditions existing in Αttica at theend of 17th – beginning of 18th century, which led the monastery of Ρentelito this difficult situation: the invasion of Venitians, the Venitian occupationand subsequent withdrawal, the invasion of the Οttoman troops, the plunderof monasteries. Μoreover this article makes an effort to analyse the tax regimeto which the monastery of Ρenteli was liable, correlating it with its honey productionas well as the overall honey production of Αttica.Τhis practice seems to have come to a dead end, leading the abbot Gregoriosaway from Αttica, and finally in Venice, at the Ρublic Βank (Ζecca) ofwhich the monastery had deposited a sum of money.